What price the foreign dollar? A study on how non-democratic countries can attract foreign direct investment - Yang, Jason Siew San (2015)
Political systems of a country have been suggested as influencing the amount of FDI inflows received by a country, with democracies being suggested as having an edge. However, some autocratic countries have attracted world-leading amounts of FDI inflows, and this raises the question of how they do so. I refer to existing literature on factors which attract FDI, and suggest that high levels of performance in these factors can be present in both democracies and autocracies. I also elaborate on policies which literature suggest attract FDI inflows, and note the literature which associates social costs with these policies. I suggest that autocracies can attract FDI inflows through the greater flexibility in policy implementation, due to their greater ability to manage the social costs associated with the different policies. To support this hypothesis, I refer to evidence from two case studies in Singapore and Hong Kong, and I suggest that their respective governments' secure positions in power have allowed for them to implement policies which were important in attracting FDI, but socially unpopular.